PENGARUH LAMA PENYIMPANAN DAUN SALAM KOJA (Murraya koenigii (L) Spreng) TERHADAP TOTAL FENOL DAN AKTIVITAS ANTIBAKTERI PADA PERTUMBUHAN Salmonella enteritidis ATCC 13067 - Abigail Jonathan, Berilin; Ekawati, Gusti Ayu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i04.p03, 2020)
This study aims to determine the effect of storage duration of curry leaves (Murraya koenigii (L) Spreng) on the total phenols and antibacterial activity of Salmonella enteritidis ATCC 13067, and the appropriate storage duration of curry leaves to produce the highest total phenols and the antibacterial activity. This study used a Completely Randomized Design (CRD) with treatment duration of storage that is 0, 3, 6, 9, and 12 days. The treatment was repeated 3 times to produced 15 experimental units. Data were analyzed by analysis of variance (ANOVA), if each treatment had a difference then preceded with the Duncan Test. The observed variables were total phenols and antibaterial activity S. enteritidis ATCC 13067. Qualitative testing showed that curry leaves extract positively containing phenols. The storage duration of curry leaves significantly affected the total phenols and antibaterial activity of S. enteritidis ATCC 13067. The best treatment was produced in the treatment without storage with the highest total phenols was 3,598.17 mg / 100g and the highest antibaterial activity power was -1,321 log cycles or 95.16% mortality bacteria.